A systematic review into the effectiveness of teaching phonics in english as a foreign language - Albalooshi, E (2024)
This study investigates the effectiveness of phonics instruction in teaching English as a Foreign Language (EFL). A systematic review of 25 studies was conducted, involving participants from diverse linguistic backgrounds. The methodology adhered to the PRISMA guidelines, with studies selected based on strict inclusion criteria that focused on decoding, fluency, and reading comprehension outcomes. Given the heterogeneity in the studies reviewed, a narrative synthesis approach was employed to summarise the findings and provide an overview of the state of knowledge regarding phonics instruction for English as a foreign language. This systematic review examined the efficacy of phonics instruction on literacy outcomes among EFL/ESL learners. The findings demonstrate that systematic phonics instruction significantly improves key literacy skills, including decoding, reading fluency, comprehension, and vocabulary acquisition. Effect sizes varied based on learner characteristics, with larger gains observed among younger children and those from Roman script backgrounds, while learners from non-Roman script backgrounds faced greater challenges. Emerging instructional trends, such as technology integration and translanguaging, also showed promising results, highlighting the adaptability of phonics instruction across different linguistic and educational environments.